The Prison and the Gallows The Politics of Mass Incarceration in America - Gottschalk, Marie (Cambridge University Press, 2013)
This project was punctuated with great joy and sadness. It coincided with the death of my mother Sally Gottschalk, who succumbed to breast cancer in February 2002. I dedicate this book to her in admiration of her great strength in the face of all the adversity she faced during and at the end of her life. In the course of writing this book, my daughter Tara went from being a struggling, ill infant to a thriving six-year-old who has boundless good cheer and who is more aware of prisons than she probably ought to be at her age. My deepest love and thanks to Tara and Atul, my toughest and most forgiving critics